Innovative Physics Education in Low-Resource Settings: A Review of Context Based, Low Cost, and Technology Enhanced Strategies in Ethiopia - Belay Sitotaw Goshu; Muhammad Ridwan (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2026)
Physics education in Ethiopia faces persistent challenges including inadequate laboratories, theory‑heavy instruction, teacher shortages, and low student motivation, constraints shared across many low‑resource settings in Sub‑Saharan Africa and South Asia. This review synthesises peer‑reviewed evidence on three innovative strategies, context‑based teaching, low‑cost DIY experiments, and technology‑enhanced learning that aim to improve physics education outcomes in resource‑limited Ethiopian schools. A systematic search of Scopus, ERIC, Google Scholar, and African Journals Online was conducted for studies published between 2010 and 2026. Inclusion criteria required peer‑reviewed empirical research focused on Ethiopia or analogous low‑resource contexts. Thematic synthesis was used to extract and integrate findings. Findings: Context‑based instruction (e.g., Cambridge‑Bahir Dar collaboration) increases relevance and engagement. Low‑cost DIY kits (e.g., WS2 initiative) reached over 8,100 students across eastern Africa, with 62% girls and high enjoyment ratings (4.81/5). PhET simulation studies in Ethiopia consistently show significant conceptual gains. Blended virtual‑physical labs produce the most balanced improvements across learning outcomes. Teacher professional development is most effective when paired with student workbooks and sustained follow‑up. Low‑resource settings need not emulate Western laboratory models; locally‑grounded, affordable, and technology‑enhanced innovations can effectively address systemic barriers. Different learning outcomes develop independently, requiring explicit instructional design. Ethiopia’s Ministry of Education should integrate low‑cost experiment construction into the curriculum, establish regional maker hubs, invest in sustained teacher training, and revise assessment to include practical skills.